Identifying Barriers to and Facilitators of Using a Mobile Fruit and Vegetable Market Intervention Delivered to Low-Income Housing Sites: A Concept Mapping Study. (February 2022) - Dulin, Akilah; Mealy, Rachel; Whittaker, Shannon; Cardel, Michelle; Wang, Jeremy; Risica, Patricia M.; Gans, Kim
Background: Mobile fruit and vegetable (F&V) markets may be a promising strategy to improve F&V intake among low-income and racial/ethnic minority groups. However, challenges remain in terms of maximizing the reach and utilization of such markets. Therefore, this study identifies perceived barriers to and facilitators of utilizing a mobile F&V market among residents who lived in low-income housing that received the markets. Specifically, this article reports the results of the follow-up acceptability study of the "Live Well, Viva Bien" (LWVB) intervention. Method: We conducted concept mapping with residents in housing communities that received the Fresh to You (FTY) markets. Participants generated, sorted, and rated statements concerning barriers to and facilitators of market use. We compared the rating data by residents' level of market utilization and created a map representing how statements clustered into conceptual themes. Results: We retained 66 unique participant-generated statements. Eight thematic clusters emerged; four pertained to barriers: financial/promotion, produce-related, scheduling/knowledge, and logistic/awareness barriers, and four related to facilitators: produce/staffing, promotion, accessibility, and multilevel market facilitators. There was a strong correlation in ratings between participants who more frequently versus less frequently shopped at the markets ( r = 0.94). Conclusions: Participants identified financial barriers, market promotion, ease of market accessibility, produce variety and quality, and staffing as key factors influencing FTY market use. This study highlights the importance of identifying the perceived barriers to and facilitators of mobile F&V market use among target populations to inform future efforts to scale up such approaches.